2001
DOI: 10.2165/00019053-200119050-00007
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Selective Decontamination of the Digestive Tract in Liver Transplant Patients

Abstract: SDD leads to the additional costs of SDD medication and routine cultures, whereas no savings in other costs and no improvement in infection episodes are realised. Consequently, SDD may be considered as a nonefficient approach in patients undergoing liver transplantation. The additional costs of severe infection are considerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Furthermore, alternative strategies have to be studied. Ideally, such a strategy would be at least as effective as SDD but less costly [74] and without risk of developing microbial drug resistance [75]. …”
Section: Antibiotic Prophylaxismentioning
confidence: 99%
“…Furthermore, alternative strategies have to be studied. Ideally, such a strategy would be at least as effective as SDD but less costly [74] and without risk of developing microbial drug resistance [75]. …”
Section: Antibiotic Prophylaxismentioning
confidence: 99%
“…Van der Voort et al [18] showed no effect of SDD and similar costs in ventilated patients in the ICU. In liver transplanted patients, SDD showed no benefits and additional costs [19]. These studies show that in high-risk patients (ICU), SDD generates the same or less costs, or no benefit (liver-transplanted patients) and higher costs.…”
Section: Discussionmentioning
confidence: 76%
“…SDD in patients undergoing liver transplantation has been estimated at $3100 USD (1997) per patient, inclusive of medication and surveillance cultures. (van Enckevort et al, 2001) Concern about costs of SDD needs to be balanced with cost savings from reducing HAIs At least four randomised controlled trials showing a lower cost per survivor when SDD was used. (Korinek et al, 1993, Rocha et al, 1992, Sanchez Garcia et al, 1998, Stoutenbeek et al, 1996 In a before-after study of antibiotic resistance and costs associated with SDD, no differences were reported in the total of ICU variable costs, microbiological and antibiotic costs between the 12 month period preceding the introduction of SDD and the 12 months thereafter.…”
Section: Discussionmentioning
confidence: 99%